Geochemistry and petrology of howardite Miller Range 11100: A lithologically diverse piece of the Vestan regolith. (17th October 2016) - Gregory, Timothy; Joy, Katherine Helen; Strekopytov, Stanislav; Curran, Natalie Mary
Abstract: The howardite‐eucrite‐diogenite (HED) clan of meteorites, which most likely originate from the asteroid Vesta, provide an opportunity to combine in‐depth sample analysis with the comprehensive remote‐sensing data set from NASA's recent Dawn mission. Miller Range (MIL) 11100, an Antarctic howardite, contains diverse rock and mineral fragments from common HED lithologies (diogenites, cumulate eucrites, and basaltic eucrites). It also contains a rare pyroxferroite‐bearing lithology—not recognized in HED until recently—and rare Mg‐rich (Fo86‐91 ) olivine crystals that possibly represent material excavated from the Vestan mantle. Clast components underwent different histories of thermal and impact metamorphism before being incorporated into this sample, reflecting the diversity in geological histories experienced by different parts of Vesta. The bulk chemical composition and petrography of MIL 11100 suggest that it is akin to the fragmental howardite meteorites. The strong lithological heterogeneity across this sample suggests that at least some parts of the Vestan regolith show heterogeneity on the mm‐scale. We combine the outcomes of this study with data from NASA's Dawn mission and hypothesize on possible source regions for this meteorite on the surface of Vesta.